Advances in Personalized Therapy: Co-targeting Intracellular Immune checkpoints in Controlling Acute Myeloid Leukemia - Kumar, Sunil; Ashraf, Muhammad Umer; Aman, Ashok Kumar; Bae, Yong-Soo (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Personalized therapy is gaining high attention due to more specific targeted approach as compared to the other conventional therapeutics. In recent decades a significant success has been seen in controlling certain sub-types of leukemia by employing precision medicines. This chapter summarizes how personalized therapies are incredibly recognizing specific tumor antigens and playing a significant role in controlling hematological disorders, especially acute myeloid leukemia (AML). We have described progress in biosimilar antibody engineering and CAR T-cell engineering in controlling relapsed AML. Moreover, the combined effect of immune checkpoint targeted therapy has been also discussed in further strengthening the efficacy of biological drugs. In addition to this, we have explained how epitranscriptomics could be used as a potential “intracellular checkpoint” target in improving the efficacy of immune cells under the tumor microenvironment. Epitranscriptomics is defined as a physiological changes or modifications in the cells by targeting m6A-modifiers (writer/editor, remover/eraser and reader/effector) without changing RNA/DNA sequence. Targeting these machineries could have high therapeutic value in controlling early progress of the disease and can be reformable into druggable candidate. Taken together, we have highlighted the advancement in personalized therapy by demonstrating the role of bi-specific biosimilar antibodies, CAR T-cell therapy and epitranscriptomics in prolonging the survival of AML patients.